Responsible board leadership - the potential value of coaching - Malan, Daniel (Haupt Verlag, 2020)
This publication explores responsible board leadership in a digital age, the topic of the year for 2018 of the International Center for Corporate Governance (ICfCG). The project kicked off at the 2017 Research Workshop on Corporate Governance of the European Institute of Advanced Studies in Management (EIASM). Here three eminent scholars and practitioners in the field – Tom Donaldson (Wharton School, University of Pennsylvania), Bob Garratt (University of Stellenbosch Business School and Cass Business School), and Lee Howell (World Economic Forum) explored the topic in a lively panel discussion. A summary of the panel discussion is included as the final chapter of this publication. The modern business environment is both complicated and complex, with the Fourth Industrial Revolution adding new challenges by blurring the lines between the physical, biological, and digital worlds. Now, with an increasing rate of change due to rapidly developing technology, and accompanied by new ethical dilemmas associated with this new context, boards of directors are often ill-prepared to manage the so-called director’s dilemma − to lead their enterprise into the future while still keeping it under prudent control. This book brings together the views of established and emerging scholars in the field. The first four contributions focus on the broader concepts of responsible board leadership, board maturity, and the value of business. In the final part, the focus shifts to the impact of the digital age on governance, leadership, and communication.
Responsible Board Leadership in a Digital Age
PUBLISHED
Switzerland
Keywords: Digital Engagement; Digital Humanities; Corporate Governance